Relationship Between GERD Comorbidity and The Severity of Nocturnal Asthma Symptoms: A Systematic Review - Zaid Hidayah; Ammar Hidayah; Islamiah Nur Insani; Fathin Hidayah (International Medical Journal Corp. Ltd, 2026)
Background: Gastroesophageal reflux disease (GERD) and asthma are common comorbid conditions, but the specific impact of GERD on the severity of nocturnal asthma symptoms remains debated. Methods: This systematic review synthesized evidence from 80 studies, including randomized controlled trials (RCTs), etc. We focused on the prevalence of GERD in asthma, the strength of association with nocturnal symptoms, pathophysiological mechanisms, and treatment outcomes. Results: The weighted average prevalence of GERD symptoms in asthma patients was 59.2% vs. 38.1% in non-asthmatics (p<0.001). Nocturnal GERD (nGER) was independently associated with new asthma onset (OR 2.3, 95% CI 1.1–4.9) and incident wheeze (OR 2.18, 95% CI 1.60–2.98). Bidirectional epidemiological data showed GERD increased asthma risk (HR 1.46, 95% CI 1.42–1.49) and asthma increased GERD risk (HR 1.36, 95% CI 1.33–1.39). Mechanistically, esophageal acid perfusion induced bronchoconstriction via vagal reflex and microaspiration. Surgical antireflux therapy reduced nocturnal exacerbations (74.9% improvement vs. 9.1% with medical therapy, p<0.001). However, proton pump inhibitors (PPIs) showed no significant improvement in morning PEF (WMD 8.68 L/min, 95% CI -2.02 to 19.37, p=0.11) in unselected asthmatics. Obesity and obstructive sleep apnea (OSA) were major confounders; in obese asthmatics, OSA rather than GERD drove nocturnal symptoms. Discussion: The apparent paradox between strong epidemiological associations and weak PPI treatment effects is explained by non-acid reflux mechanisms, patient heterogeneity, and colinear comorbidities.Conclusion: Nocturnal GERD significantly increases asthma severity and incidence, but PPI therapy benefits only symptomatic, confirmed GERD subgroups. Surgical fundoplication and CPAP (in OSA+GERD) improve nocturnal asthma outcomes.